Kenya : Technical Assistance Report-Improving the Quality of Fiscal and Public Debt Data (October 7-16, 2019). - International Monetary Fund. Statistics Dept. (Washington, D.C. : International Monetary Fund, 2021)
In response to a request from the Government of Kenya, an AFRITAC East (AFE) government finance statistics (GFS) technical assistance (TA) mission was conducted in Nairobi, Kenya, during October 7-16, 2019. The primary objective of the mission was to support staff in improving the quality of fiscal and public debt data for the general government and migration of the fiscal framework to Government Finance Statistics Manual 2014 (GFSM 2014) concepts to facilitate fiscal and debt policy analysis for improved public financial management. This is a continuation of the ongoing efforts in capacity development aimed at supporting member countries to adopt the GFSM 2014 and the Public Sector Debt Statistics Guide (PSDSG 2011).
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Kenya